AB1192 THE UNDERWORLD OF DEPRESSIVE SYMPTOMS IN RHEUMATIC DISEASES: OVERLOOKED, UNRECOGNIZED OR UNPERCEIVED?. (2nd June 2020) - Ingegnoli, F.; Schioppo, T.; Ubiali, T.; Bollati, V.; Ostuzzi, S.; Buoli, M.; Caporali, R.
Abstract : Background: The concomitant presence of depressive symptoms and rheumatic diseases (RDs) impose a considerable economic and social burden on the communities as they are associated with numerous deleterious outcomes such as increased mortality, work disability, higher disease activity and worsening physical function, higher pain levels and fatigue. Despite growing interest on depressive symptoms burden in RDs, current patient perception on this topic is unknown. Objectives: Italian patients with RDs were invited to participate in an online study gauging the presence and the perception of depressive symptoms using the Patient Health Questionnaire (PHQ-9). Methods: This was a cross-sectional no-profit online study to screen the presence and the perception of depressive symptoms in RDs patients. All participants gave their consent to complete the PHQ-9 and they were not remunerated. Completion was voluntary and anonymous. The PHQ-9 rates the frequency of symptoms over the past 2 weeks on a 0-3 Likert-type scale. It contains the following items: anhedonia, depressed mood, trouble sleeping, feeling tired, change inappetite, guilt or worthlessness, trouble concentrating, feeling slowed down or restless, and suicidal thoughts. Patients were stratified as: <4 not depressed, 5-9 sub-clinical or mild depression, 10-14 moderate depression, 15-19 moderately severe depression and 20-27 severe depression. The survey was disseminated by ALOMAR (Lombard Association for Rheumatic Diseases) between June and October 2019. Results: 192 patients took part in the study: 170 female with median age 50 years. Among respondents only 35 (18.2%) were not depressed. Depression was sub-clinical or mild in 68 (35.4%), moderate in 42 (21.9%), moderately severe in 30 (15.6%), and severe in 17 (8.9%). 16 (8.3%) of respondents declared to have depressive symptoms and 7 of 16 were under psychiatric therapy. Moreover, patients were grouped according to diagnosis. 124 respondents had inflammatory arthritis (rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis). 23 (18.5%) were not depressed. Depression was sub-clinical or mild in 41 (33%), moderate in 26 (21%), moderately severe in 21 (17%), and severe in 13 (10.5%). Among them, 8 (6.5%) declared to have depressive symptoms depressed and 3 of 8 were under psychiatric therapy. 49 respondents had a connective tissue disease or vasculitis. 11 (22.5%) were not depressed. Depression was sub-clinical or mild in 19 (38.8%), moderate in 13 (26.5%), moderately severe in 2 (4%), and severe in 4 (8.2%). Among them, 3 (6%) declared to have depressive symptoms and 1 of 6 were under psychiatric therapy. 19 respondents had other rheumatic diseases. 1 (5.3%) was not depressed. Depression was sub-clinical or mild in 8 (42.1%), moderate in 3 (15.8%), moderately severe in 7 (36.8%). Among them, 5 (26.3%) declared to be depressed and 3 of 5 were under psychiatric therapy. Conclusion: Our study confirmed that the overall real-life burden of depressive symptoms is relevant in all RDs. At the same time, these results highlighted that depressive symptoms are overlook by physicians and unperceived by patients since fewer that half of respondents (46.4%) had a clinical depression (PHQ-9>10). These results suggested that screening for depression should form part of the routine clinical assessment of RD patients. Acknowledgments: We thank the Lombard Association of Rheumatic Diseases (ALOMAR) for its contribution to design and disseminate the survey, the group that sustain systemic sclerosis (GILS), and the IT service of the University of Milan. Disclosure of Interests: Francesca Ingegnoli: None declared, Tommaso Schioppo: None declared, Tania Ubiali: None declared, Valentina Bollati: None declared, Silvia Ostuzzi: None declared, Massimiliano Buoli: None declared, Roberto Caporali Consultant of: AbbVie; Gilead Sciences, Inc.; Lilly; Merck Sharp & Dohme; Celgene; Bristol-Myers Squibb; Pfizer; UCB, Speakers bureau: Abbvie; Bristol-Myers Squibb; Celgene; Lilly; Gilead Sciences, Inc; MSD; Pfizer; Roche; UCB